Wide Field Retinal Imaging –In Diagnosing of Retinal Pathologies - Richa Ranjan; Neha Bharti; Bhupesh Singh (Delhi Journal of Ophthalmology)
The peripheral retina is affected by many retinal pathologies. However, its documentation until recently was limited even with the montaging techniques available in the traditional fundus cameras. The invention of wide-field and ultra-wide-field imaging systems has helped in the documentation as well as an understanding of many retinal pathologies involving the peripheral retina. This article aims to highlight the importance of wide-field retinal imaging in the diagnosis and management of peripheral retinal pathologies.